Pseudoaneurysm of facial artery after bilateral sagittal split osteotomy, complicated by infection after embolization. Issue 6 (November 2016) - Cho, Jungsuk; Kim, Jay; Israel, Howard; Momtahen, Shabnam; Behrman, David
Abstract: This is a case report regarding the postoperative complication of pseudoaneurysm of the facial artery likely due to mechanical injury after a bilateral sagittal split osteotomy (BSSO). This article will discuss diagnosis, management, embolization therapy using Onyx (ethylene vinyl alcohol copolymer in dimethyl sulfoxide – DMSO) and review the literature on pseudoaneurysm formed after bilateral sagittal split osteotomy. We will also discuss the common embolic agents and apparent adverse reaction of local infection that may be due to the presence of residual Onyx in the soft tissues.